Antibacterial Activity of Some Lactic Acid Bacteria Isolated From Milk Products Against Streptococcus pyogenes and Staphylococcus aureus Causing Tonsillopharyngitis: Aktivitas Antibakteri Beberapa Bakteri Asam Laktat yang Diisolasi dari Produk Susu Terhadap Streptococcus pyogenes dan Staphylococcus aureus Penyebab Tonsilofaringitis - Naser, Rana Hussein; Algburi, Ammar Riyadh; Popov, Igor (Indonesian Journal on Health Science and Medicine, 2025)
Background: Tonsillitis and pharyngitis are the most common oral infections accompanied by risky complications, including infection recurrence and antibiotic resistance. Streptococcus pyogenes and Staphylococcus aureus are the predominant cause of such infection. Objective: This study comes to investigate the nature of bacterial interactions between probiotic lactobacilli and bacilli, isolated from milk products, with the most common pathogenic bacteria causing tonsillitis and pharyngitis in human. Methods: A 20 samples of local milk products were collected. in addition to 25 tonsil swabs were collected from patients with tonsillopharyngitis. VITEK system2 was used to confirm bacterial identification. The antibiotic susceptibility of bacterial isolates was evaluated to five tested antibiotics. Co-aggregation capability of tested bacterial species was evaluated to investigate the nature of bacterial interactions towards each other. Results: Of the 20 milk samples, the VITEK2 system confirmed that 3 (60%) of bacterial growth were identified as Bacillus subtillus while 8 (72.7%) were Lactobacillus plantarum. On the other hand, 11 (73.3%) of bacterial growth were Streptococcus pyogenes and 6 (100%) were Staphylococcus aureus isolated from tonsillopharngitis patients. The isolated S. pyogenes and S. aureus were highly resistant to the tested antibiotics, but not to vancomycin. Both bacilli and lactobacilli species showed high co-aggregation scores with the isolated pathogenic bacteria. Conclusions: The antibiotic resistance of pathogenic bacteria requires urgent, safe, and effective alternative antimicrobial agents. Beneficial bacteria capable to compete with the growth of pathogens and inhibit their growth, eventually, preventing such infections. Highlights: Antibiotic-resistant S. pyogenes and S. aureus cause recurrent tonsillopharyngitis. Milk-derived L. plantarum and B. subtilis co-aggregate with pathogens, inhibiting colonization. Probiotics offer a natural alternative for preventing antibiotic-resistant infections. Keywords: Tonsillopharyngitis, Streptococcus pyogenes, Staphylococcus aureus, bacilli and lactobacilli, auto-aggregation and co-aggregation.